Entrepreneurship Processes: Digital Self-Efficacy, Technostress, and Entrepreneurial Behaviour in South Africa: A Critical Review - Utami Tunjung Sari; Bhenu Artha; Antonius Satria Hadi; Bahri Bahri; Niken Permata Sari; Ascasaputra Aditya; Cahya Purnama Asri (Journal of Literature Review, 2026)
This study provides a critical review of the research by Simba, Rambe, and Jones (2025) concerning the interplay between digital self-efficacy, technostress, and entrepreneurial intention among early-stage entrepreneurs in South Africa. Grounded in the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM), the study examines how digital tools influence entrepreneurial processes within a non-Western context. The methodology utilizes a critical review design to systematically evaluate the conceptual frameworks and empirical findings of the original work. Results indicate several strengths, including a novel theoretical interface and a robust sample of 643 respondents. However, significant limitations were identified, most notably the non-significant effect of technostress on entrepreneurial intention and a heavy reliance on university student samples, which may conflate education with actual practice. The review concludes that while the original study offers valuable indigenous theorization, its practical utility is constrained by inconclusive primary findings and limited generalizability beyond South Africa. Future research should employ longitudinal mixed-methods and broader African samples to better capture the temporal dynamics of technology-driven entrepreneurship.